Variation in contributions to teaching by meerkats - Thornton, Alex (The Royal Society, 2008)
Recent evidence from cooperative insect, bird and mammal societies has challenged the assumption that teaching is restricted to humans. However, little is known about the factors affecting the degree to which individuals in such societies contribute to teaching. Here, I examine variation in contributions to teaching in meerkats, where older group members teach pups to handle difficult prey. I show that investment in teaching varies with characteristics of pups, helpers, groups and ecological conditions. Although prior experience in caring for pups did not significantly influence teaching behaviour, younger helpers, which were still investing in growth, contributed less to teaching than older individuals. This suggests that, in common with other cooperative activities, contributions to teaching vary with the costs experienced by individual group members. However, in contrast to other forms of helping in meerkats, I detected no effects of nutritional state on teaching, suggesting that it carries relatively low costs. In species where individuals can potentially gain direct or indirect fitness benefits from facilitating learning in others, low costs divided among multiple group members may help tip the balance towards selection for teaching.